Analisis Kepemimpinan Transformasional Terhadap Kinerja Karyawan Di Departemen Procurement Pt. X - Sutrisno, Sutrisno; Sibarani, Mentiana (Riviera Publishing, 2025)
Leadership is one of the key factors determining the success of an organization. Leaders who lack the ability to guide and direct their teams effectively often fail to achieve organizational goals. This can lead to low productivity and efficiency within the company. Therefore, it is essential for organizations to have quality leaders who can inspire and motivate employees to work optimally. This study aims to analyze the impact of transformational leadership on employee performance in the Procurement Department of PT X, a pulp and paper manufacturing company. The Procurement Department plays a strategic role in supporting production continuity through the procurement of goods and services, including the conversion of Purchase Requests (PR) into Purchase Orders (PO). This research employs a quantitative approach with a survey method targeting employees in the department. Data analysis was conducted using simple linear regression manually to examine the relationship between leadership style and employee performance. The findings of this study are expected to contribute to the development of effective leadership strategies to improve individual and organizational performance.